Pengaruh Pemasaran Media Sosial dan E-Wom Terhadap Minat dan Keputusan Berkunjung Ke Wisata Pulau Beras Basah - Lukman Hakim; Gusti Noorlitaria Achmad (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine the impact of social media marketing and electronic word-of-mouth (e-WOM) on the intention and decision to visit the Beras Basah Island tourist destination. A quantitative method was emplJeoyed to analyze the issues, with a sample of 160 visitors to the Beras Basah site in Bontang. Data collection techniques included document analysis, observation, and questionnaires utilizing a Likert scale. Path coefficient analysis was conducted using SmartPLS 4.0. The results indicate that: 1) social media marketing has a positive and significant effect on visit intention; 2) e-WOM has a positive and significant effect on visit intention; 3) social media marketing has a positive and significant effect on the visit decision; and 4) e-WOM has a positive but insignificant effect on the decision to visit the Beras Basah tourist destination in Bontang City.